Processing waste: bioactive components and antioxidant capacity of cold-pressed oils from some fruit seeds - Aleksandra ĆIRKOVIĆ; Mirjana DEMIN; Milica FOTIRIĆ AKŠIĆ; Biljana RABRENOVIĆ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
In this study, the possible use of seeds after fruit processing to obtain unconventional cold-pressed edible oil was investigated. For this purpose, seeds of quince, sour cherries and plum were used. Fatty acid composition, antioxidant activity, peroxide and acid value, oxidative stability, and tocopherols and phytosterols content were determined in the studied oils. Plum seed oil was dominated by oleic acid, while quince and sour cherry seed oils contained abundant linoleic acid. The total polyphenol content in the studied oils ranged from 2.28 to 9.03 mg GAE 100 mL-1. Antioxidant properties (ABTS, DPPH, FRP) were associated with tocopherol content. All three studied oils were rich in β-sitosterol. The oxidative stability of the studied oil samples varied and ranged from 1.92 h-31.17 h. Quince seed oil had the highest content of α-tocopherol (44.30 mg 100 g-1) and plum seed oil had the lowest (3 mg 100 g-1), while sour cherry seed oil had the highest content of β+γ-tocopherol (17.19 mg 100 g-1). The results show that oil from quince, sour cherry, and plum seeds is suitable for the production of a high quality cold-pressed oil. The use of this type of waste from fruit processing contributes to waste reduction and promotes the circular economy.